Effectiveness of tixagevimab/cilgavimab in patients with hematological malignancies as a pre-exposure prophylaxis to prevent severe COVID-19: a Czech retrospective multicenter study - Demel, Ivo; Skopal, David; Šafránková, Eliška; Rozsívalová, Petra; Jindra, Pavel; Šrámek, Jiří; Turková, Adéla; Vydra, Jan; Labská, Klára; Vedrová, Jana; Čerňan, Martin; Szotkowski, Tomáš; et al. (Annals of hematology, 2024)
Despite lower virulence, the omicron variant of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) that causes coronavirus disease 2019 (COVID-19) still poses a relevant threat for immunocompromised patients. A retrospective multicentric study was conducted to evaluate the efficacy of pre-exposure prophylaxis with tixagevimab/cilgavimab (Evusheld) with a 6-month follow-up for preventing severe COVID-19 in adult patients with hematology malignancy. Among the 606 patients in the cohort, 96 (16%) contracted COVID-19 with a median of 98.5 days after Evusheld administration. A total of 75% of patients had asymptomatic or mild severity of COVID-19, while just 25% of patients with SARS-CoV-2 positivity had to be hospitalized. Two patients (2%) died directly, and one patient (1%) in association with COVID-19. Eight patients (1.3%) of every cohort experienced adverse events related to Evusheld, mostly grade 1 and of reversible character. It was found that complete vaccination status or positive seroconversion was not associated with lower risk of COVID-19 infection. Previous treatment with an anti-CD20 monoclonal antibody was associated with higher rates of COVID-19, while previous treatment with anti-CD38 monoclonal antibody was not, as was the case for recipients of hematopoietic stem cell transplantation or CAR-T cell therapy. Presence of other comorbidities was not associated with more severe COVID-19. The results support the growing evidence for Evusheld's efficacy against severe COVID-19 in patients with hematology malignancies.
Keywords: hematologické nádory; monoklonální protilátky; Antibodies, Monoclonal; Adult; dospělí; COVID-19; preexpoziční profylaxe; retrospektivní studie; Pre-Exposure Prophylaxis; Humans; Česká republika; SARS-CoV-2; lidé; Hematologic Neoplasms; Retrospective Studies; Czech Republic